THE USE OF FENUGREEK HAY AND CLOVER BLUE AS INGREDIENTS FOR PRODUCTION OF FUNCTIONAL FOOD PRODUCTS - Oleg Mihailovich Lavrov; Tatiana Nikolaevna Lavrova (Современная наука и инновации)
The article gives a review about advantages of use of nonconventional vegetable raw materials, fenugreek hay and Greek as an ingredient for the production of functional food products. As a result of the analytical literature review to identify opportunities for the use of fenugreek on various kinds of biological (pharmacological activity).